Pengaruh Ibadah Haji dan Umrah Terhadap Spiritual, Sosial, dan Ekonomi Umat Muslim - Nayla Zafira Indra; Hasbi Ash-Shadiqin; Intan Cahya Iskandar; Eza Fira Dahrani; Satrio Syahbana; Wismanto Wismanto (Student Scientific Creativity Journal, 2025)
The Hajj and Umrah are spiritual rituals that have a special place in Islam, with essential differences in terms of the time of implementation. Hajj, as one of the pillars of Islam, is obligatory for every Muslim who is physically and financially able to perform it at least once in a lifetime. Umrah, although sunnah, also has great virtue in getting closer to Allah SWT. This study aims to analyze both forms of worship from the perspective of history, fiqh (Islamic law), and their social and spiritual influences on Muslim individuals and communities, providing a comprehensive understanding of the procedures, laws, and wisdom of implementing the Hajj and Umrah, as well as to examine the impact of implementing the Hajj and Umrah in everyday life, both from the perspective of individual spirituality and from the social side of Muslims. The method used in this study is qualitative research with a descriptive analysis approach. Data obtained from reference books, academic journals, and articles. The analysis was carried out with a descriptive and araitis approach explaining the theological perspective of Islamic law and the social and spiritual impacts of worship. The results of this study indicate that Hajj and Umrah have a significant impact on building deep spiritual awareness among Muslims. Ritually, the procedures for carrying out these two worships illustrate the values of monotheism, equality, and sacrifice. From an Islamic legal perspective, the difference between the obligation of Hajj and the sunnah of Umrah provides flexibility for Muslims to get closer to Allah SWT whenever they are able. From a social perspective, the implementation of this worship is a means of strengthening the unity of Muslims from all over the world.